Description of a new genus and two new species of Forsteriini Tippmann, 1960 from Peru (Coleoptera, Cerambycidae, Lamiinae) - Audureau, Alain; Santos-Silva, Antonio (Zootaxa, 2019)
A new genus and two new species of Forsteriini Tippmann, 1960 (Coleoptera, Cerambycidae, Lamiinae) are described from Peru: Obereoides peruviensis sp. nov., and Morvanica demezi, gen. nov., sp. nov.. A key to species of Obereoides Fisher, 1938 is provided. Morvanica is included in a previous key to genera of the tribe.